Addition of Cold Milling Waste to Increasing Compressive Strength and Water Absorption in Batako - Syahputra, Damario Aji; Devi, Rida Handiana; Marwahyudi, Marwahyudi (ASTONJADRO, 2025)
The development of construction in Indonesia drives the need for more efficient and environmentally friendly building materials. One of the proposed innovations is the utilization of cold milling asphalt waste as a mixture of fine aggregate in making bricks. This study aims to determine the effect of variations in the addition of asphalt waste on the compressive strength and water absorption of bricks. The problems raised in this study include how variations in the addition of asphalt waste to bricks affect their mechanical properties. The study was conducted experimentally by making 12 brick samples measuring 30 x 15 x 10 cm using variations in asphalt waste mixtures of 0%, 20%, 25%, and 30%. Testing included compressive strength and water absorption tests at the ages of 7 and 28 days. The results showed that the addition of asphalt waste affected the characteristics of bricks. In a mixture of 30%, bricks showed the highest compressive strength value of 7.9 MPa after 28 days, while water absorption increased with increasing percentage of asphalt waste. These results indicate that asphalt waste can be used as a partial substitute for sand in making bricks without significantly reducing their structural strength. The novelty of this research lies in the use of cold milling asphalt waste which has not been widely applied to brick materials. This study concludes that cold milling asphalt waste can be used as a mixture in brick production to reduce construction waste while supporting the concept of sustainable development. This innovation provides a solution for construction entrepreneurs in creating more economical and environmentally friendly products.